Structure evolution during uniaxial tensile deformation of high density polyethylene before and after irradiation by 1 MeV electrons. Issue 10 (19th December 2013) - Rui, Erming; Yang, Jianqun; Li, Xingji; Liu, Chaoming; Tian, Feng; Gao, Feng; Li, Xiuhong; Geng, Hongbin
Abstract The structural evolution of high density polyethylene (HDPE) during uniaxial tensile deformation, before and after irradiation by 1 MeV electrons, is in situ studied by synchrotron small angle X‐ray scattering (SAXS) and wide angle X‐ray diffraction (WAXD). Both the pristine and the irradiated HDPE exhibit three regions of deformation behavior. It is shown that the deformation in the first region is in accord with the change in long period of the lamellar structure. In the following two regions, both the strain‐induced melting and strain‐induced crystallization could occur. The tensile stress decreases with strain in the second region due to the dominant melting effect. In the third region, the synergistic effect of the melting and crystallization results in stress leveling off first, and then the tensile stress increases again because the crystallization effect becomes dominant at higher strains. For the irradiated HDPE, the irradiation‐induced crosslinking network slows down the deformation process. Compared to the pristine one, all the tensile stress is rather higher at a given strain for the irradiated HDPE. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40269.